Suppose x ≥ 0. Then
x² = y⁴ (1 - y³) ⇒ x = √(y⁴ (1 - y³)) = y² √(1 - y³)
On the other hand, if x < 0, then
x² = y⁴ (1 - y³) ⇒ x = - y² √(1 - y³)
Either expression for x in terms of y describes half of the curve, to either side of the y-axis (i.e. the line x = 0).
Find where these two curves intersect:
y² √(1 - y³) = - y² √(1 - y³)
2y² √(1 - y³) = 0
2y² = 0 or √(1 - y³) = 0
y = 0 or 1 - y³ = 0
y = 0 or y³ = 1
y = 0 or y = 1
So, the two halves meet at the points (0, 0) and (0, 1).
The area between the halves is then given by the integral
![\displaystyle \int_(y=0)^(y=1) \left(y^2√(1-y^3) - \left(-y^2√(1-y^3)\right)\right) \, dy](https://img.qammunity.org/2023/formulas/mathematics/college/ovw1bpsl6qcybseysa0esb90avl1tgncuq.png)
Let's calculate it:
![\displaystyle \int_(y=0)^(y=1) 2y^2 √(1-y^3) \, dy](https://img.qammunity.org/2023/formulas/mathematics/college/t0jyyttkxvjwe6255flnhqvvbwkqp30pif.png)
Substitute z = 1 - y³ and dz = -3y² dy.
![\displaystyle \int_(z = 1 - 0^3)^(z = 1 - 1^3) -\frac23 √(z) \, dz](https://img.qammunity.org/2023/formulas/mathematics/college/zwitequuk4ncb3qs7mqo0sc75d6ayxkjx1.png)
![\displaystyle -\frac23 \int_(z = 1)^(z = 0) √(z) \, dz](https://img.qammunity.org/2023/formulas/mathematics/college/g6hf1mwbnn80mpqkdqemajqwq1j32mxy61.png)
![\displaystyle \frac23 \int_(z = 0)^(z = 1) z^(1/2) \, dz](https://img.qammunity.org/2023/formulas/mathematics/college/twdbzaubze1ew275caxzkozbe0ng7p08dc.png)
![\displaystyle \frac23 \left(\frac23 z^(3/2)\right) \bigg|_(z=0)^(z=1)](https://img.qammunity.org/2023/formulas/mathematics/college/wg0fetlllurwargu32rt0fk8ps8hv7c1rw.png)
![\displaystyle \frac49 z^(3/2) \bigg|_(z=0)^(z=1)](https://img.qammunity.org/2023/formulas/mathematics/college/31coolp2v05509lhg5rqt41a2t02475ys2.png)
![\displaystyle \frac49 \cdot 1^(3/2) - 0 = \boxed{\frac49}](https://img.qammunity.org/2023/formulas/mathematics/college/kmmk9r9heghihmnajrmm1g8e6j748bn9rg.png)